The role of spine adipose index in predicting the risk for septic spondylodiscitis after lumbar percutaneous laser disc decompression - I. A. Stepanov; V. A. Beloborodov (Acta Biomedica Scientifica, 2023)
The aim. To analyze the role of the spine adipose index (SAI) in predicting the risk of septic spondylodiscitis after lumbar percutaneous laser disk decompression (PLDD).Material and methods. A retrospective observational single-center study was performed. Various clinical and instrumental parameters have been studied, including the spine adipose index, which are potential risk factors for the development of postprocedural septic spondylodiscitis.Results. The study included 219  patients who underwent PLDD for degenerative lumbar disk disease. The average period of postoperative observation was  30.8  ±  13.3  months. Signs of septic spondylodiscitis were detected in 5 (2.28%) cases. Multivariate analysis showed that III degree of anesthesiological risk by the American Society of Anesthesiologists (ASA) scale (p = 0.021), a high value of body mass index (more than 25 kg/m2) (p = 0.043) and a high value of SAI (over 0.7) (p = 0.037) are statistically significantly associated with the development of septic spondylodiscitis in patients who underwent lumbar PLDD.Conclusion. The value of SAI is statistically significantly associated with the development of spondylodiscitis in patients who underwent PLDD for degenerative lumbar disk disease.